Correction: Application of the comprehensive complication index and Clavien–Dindo complication classification in cardiac surgery: a retrospective study - Zhen-Rong Zhang; Yang-Zheng Li; Xiao-Qing Wu; Wen-Jun Chen; Jie-Yang Yuan; Min Yan (BMC Cardiovascular Disorders)
Abstract Background Standardized tools are needed to accurately assess the severity of postoperative complications in cardiac surgery, which is critical for patient management and outcome evaluation. This study aims to evaluate the application of the Clavien Dindo Complications Classification (CDCC) and Comprehensive Complications Index (CCI) in cardiac surgery. Methods A single-center retrospective analysis was conducted on 738 patients who underwent cardiac surgery between January 2021 and December 2023. The CDCC and CCI were used to evaluate postoperative complications. The age-adjusted Charlson comorbidity index (ACCI) and LVEF were also evaluated. Multivariate regression models according to the most severe complications (CDCC ≥ IIIb grade) were tested. We compared the CDCC and CCI with the patient’s surgical condition and economic burden and calculated the sample size required for different evaluation types. Results 563 patients (76.3%) had at least one complication. The mean CCI was 22.5 ± 19.3. Patients who underwent more complex surgeries had higher CDCC grades and CCI scores. Hospitalization cost and length of stay increased with increasing CDCC grade and CCI score. The ACCI (OR: 1.334 [1.109–1.606], p = 0.002) and LVEF (OR: 0.965 [0.943– 0.987], p = 0.002) were associated factors for the most severe complications. The CCI may reduce the required sample size by 20.5 times and 19.6 times compared with the most severe complication or major adverse cardiovascular and cerebrovascular events, respectively, as an endpoint. Conclusion The CCI and CDCC can help reflect the complexity of cardiac surgery and the burden of hospitalization, providing a more accurate assessment of surgical complications. This may reduce the sample size needed for clinical trials, thus facilitating research in cardiac surgery. Clinical trial registration Chinese Clinical Trial Registry (No. ChiCTR2400084925) on May 28th, 2024. https://www.chictr.org.cn/showproj.html?proj=228499 .